Diagnóstico del sistema de seguridad y salud en el trabajo, en la empresa “Lácteos San Isidro” del cantón Sucre - Salvatierra Zambrano, Yonny Javier (2021)
The objective of this research was to evaluate the Occupational Health and Safety system for the prevention of occupational hazards at the LÁCTEOS SAN ISIDRO Company in Sucre canton. To comply with it, a three-phase methodology was developed: the first step was to determine the current situation of the company with respect to the occupational health and safety system, through an observation visit to the company, and then carry out the a Check List to the manager of the company for subsequent analysis of the data obtained from the tool executed; as a second point, the processes related to safety and health at work in the company were evaluated through the application of a technical survey directed to employees and workers, said instrument is validated with the Delphi method, then the i obtained information was tabulated and analyzed, the occupational risks in the jobs were also identified by means of the PGV risk matrix, giving way to the determination of the existing problems; finally, an improvement plan was designed applying the 5W + 1H method and the proposal for actions to improve the Occupational Health and Safety System for the prevention of occupational risks was socialized. The results of the investigation established that the company complies with the regulatory requirements, however, the risks found are determined as moderate and important, and there are no periodic and continuous evaluations that provide an information base for the proper decision-making regarding to necessary improvements.